THE EFFECT OF EXPERIENTIAL MARKETING ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION AS AN INTERVENING VARIABLE AT IBOX MANADO TOWN SQUARE - Kimberly Virgin Langie; Paulus Kindangen; Emilia M. Gunawan (Universitas Sam Ratulangi, 2022)
The aim of this research is to analyze the effect of experiential marketing and customer satisfaction towards customer loyalty at IBOX Manado Town Square. The data used in this research is a primary data, collected from over 100 respondents who are the customers of IBOX Manado Town Square. The sampling technique used in this research is purposive sampling. The data was processed by path analysis. The results showed that the experiential marketing have directly positive and significant effect on customer loyalty at IBOX Manado Town Square and customer satisfaction have a positive and significant effect on customer loyalty at IBOX Manado Town Square. Experiential marketing indirectly have a positive and significant influence on customer loyalty through customer satisfaction at IBOX Manado Town Square.Keywords: experiential marketing, customer satisfaction, customer loyalty